O-174 The association of chromosomal abnormalities with embryo ultrastructure, spindle anomalies and metabolic profiling. (30th June 2022) - Chatzimeletiou, A; Sioga, A; Emmanouil-Nikoloussi, E.N; Petrogiannis, N; Patrikiou, A; Georgiou, I; Theodoridis, G; Virgiliou, C; Gika, E; Raikos, N; Kolibianakis, E; Nicolaides, K; et al.
Abstract: Study question: Can metabolic profiling predict embryos at risk of chromosomal abnormalities and how are these reflected in the ultrustructure and cytoskeleton? Summary answer: Different metabolic profiles are observed between normal and aneuploid/chaotic embryos which are linked to altered mitochondrial and other organelles' structure/function and spindle and nuclear abnormalities. What is known already: One of the greatest challenges in IVF is the selection of the best 'fit' embryo for implantation in a non-invasive way. Down's syndrome embryos and Monosomy 21 embryos have previously been shown to have differential expression of metabolites compared to normal embryos, but limited studies, have investigated in detail the metabolic profiling of embryos with other abnormalities in comparison to chromosomally normal embryos or their reflection in the ultrustructure and the cytoskeleton. Study design, size, duration: Culture media collected on day 3 from 200 embryos which underwent PGT-A, were analysed by hydrophilic interaction liquid chromatography tandem mass spectrometry (HILIC-MS/MS). The chromosomally normal embryos were transferred to the uterus (1–2 embryos/ET) or still remain vitrified for clinical use and 120 of the embryos that were diagnosed with chromosomal abnormalities were either processed for spindle/chromosome configurations analysis (n = 60) by confocal laser scanning microscopy(CLSM) or for ultrastructural analysis (n = 60) by Transmission Electron Microscopy(TEM). Participants/materials, setting, methods: Metabolic profiling was conducted in a Forensic Toxicology Laboratory by HILIC-MS/MS (100 metabolites). Spindle Chromosome Configuration analysis was conducted in an academic hospital after methanol fixation and immunostaining with α-tubulin, γ-tubulin, acetylated-tubulin antibodies and DAPI or/ PI to visualise DNA. Ultrastructure analysis by TEM was carried out in a Histology/Embryology Laboratory following embryo fixation in 3% glutaraldehyde, 1% osmium tetroxide, washes in  PBS and staining with 1% aqueous uranyl acetate. Main results and the role of chance: This  study provides screening  for >100 primary metabolites using HILIC-MS/MS in a single run of 40 minutes. Characteristic patient specific metabolic profiles were observed which differed between normal embryos that had resulted in a viable pregnancy and aneuploid and chaotic embryos. Logistic regression analysis revealed a number of metabolites that had a high predictive value including Isoleucine,  lysine and glucose and models were created in combination with embryo score which in the future could serve as non-invasive markers for the detection of chromosomal abnormalities before embryo transfer. TEM analysis revealed differences in the quality of cells and organelle activity which were reflected in the embryo metabolic profiles. Chaotic poor quality embryos showed a lower number of mitochondria, often with no cisternae, increased number of vacuoles, and frequently problems in junctions between cells. Aneuploid but well developed hatching blastocysts had mainly cells with good mitochondrial morphology/ activity, nice Golgi apparatus and well developed rough and smooth endoplasmic reticulum but depending on the aneuploidy involved, inner cell mass cells with limited organelles and occasionally lipofuscin droplets in the trophectoderm were evident. Nuclear and chromosomal abnormalities were interrelated through abnormalities in cytokinesis and spindle formation and reflected in the embryo metabolic profiles. Limitations, reasons for caution: Although metabolic profiles were compared between normal and chromosomally abnormal embryos identified by PGT-A, all the  normal embryos were transferred to the uterus or remain vitrified for clinical purposes and therefore the ultrastructure analysis and the spindle chromosome configuration analysis are based only on chromosomally abnormal embryos. Wider implications of the findings: This study identified distinct differences in the metabolic profiles of normal and chromosomally abnormal embryos and provides unique metabolites which in the future could serve as non-invasive biomarkers for the detection of chromosomal abnormalities before embryo transfer. Trial registration number: not applicable